2020
DOI: 10.3390/ijerph17249450
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Anxiety Levels in Pregnant and Post-Partum Women during the COVID-19 Pandemic

Abstract: The aim of this study was to analyze stress and anxiety levels experienced by pregnant and post-partum women during the COVID-19 pandemic, as well as to indicate the social and medical factors that could contribute to stress and anxiety. A total of 210 patients were enrolled in the study. Two well-established test-tools were applied: State-Trait Anxiety Inventory (STAI) and Perceived Stress Scale (PSS-10). The study revealed that the levels of stress and anxiety experienced by the surveyed patients were modera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
2
12

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(94 citation statements)
references
References 29 publications
3
60
2
12
Order By: Relevance
“…To the best of our knowledge, this is the first report on perceived stress prevalence during postpartum in Latin-American women during the COVID-19 lockdown. In our study, the mean ± SD of the total score for PSS-10 was similar to that reported in Polish women (18.4 ± 18) [27].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…To the best of our knowledge, this is the first report on perceived stress prevalence during postpartum in Latin-American women during the COVID-19 lockdown. In our study, the mean ± SD of the total score for PSS-10 was similar to that reported in Polish women (18.4 ± 18) [27].…”
Section: Discussionsupporting
confidence: 89%
“…Total scores range between 0 and 40, with higher scores indicating more perceived stress. In the present study, perceived stress was classified as low (0-13), moderate (14-26), or high (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40), as suggested by others [35,36]. The PSS-10 scale had good reliability (Cronbach's alpha = 0.89).…”
Section: Primary Outcomes and Psychological Questionnairessupporting
confidence: 50%
See 1 more Smart Citation
“…Данные относительно выраженности нарушений психического здоровья в период пандемии в связи триместрами или после рождения ребенка довольно противоречивы. В одном исследовании [25] наиболее высокие показатели тревоги характерны для женщин после рождения ребенка, в другом исследовании [14] наибольшие значения тревоги наблюдаются у женщин в третьем триместре; польские авторы отмечают большую выраженность тревоги в первом триместре [23].…”
Section: Discussionunclassified
“…Также результаты исследования свидетельствуют, что показатели личностной тревоги и стресса выше среди тех женщин, которые получали лечение в области психического здоровья (психотерапевтическое или психофармакологическое), а показатели ситуативной тревоги оказались достоверно связаны с наличием у женщины партнера: те, у кого он был, реже испытывали ситуативную тревогу. Также при сравнении уровней тревоги у женщин, находящихся в разных триместрах, было показано, что высокий уровень ситуативной тревоги испытывают женщины в первом триместре (82%), 74% -во втором триместре, и около 50% -в третьем триместре и после рождения ребенка [23].…”
Section: тревога депрессия и стресс у беременных и родивших женщин в период пандемииunclassified